2005
DOI: 10.1007/bf03183640
|View full text |Cite
|
Sign up to set email alerts
|

Reconstruction of precipitation in the last 140 years from tree ring at south margin of the Tengger Desert, China

Abstract: Based on the tree ring width index of Pinus tabulaeformis, precipitation in the last 140 years was reconstructed at south margin of the Tengger Desert. The results indicated that there were obvious fluctuations of dry-wet changes in precipitation: two wet periods occurred during 1868-1876 and 1932-1939, and two dry periods during 1877-1894 and 1924-1932, however, the years 1887 and 1888 were a little wet. There were small changes in precipitation during 1895-1923 and 1940-2000. As compared to the average, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 5 publications
3
11
0
Order By: Relevance
“…Inversely, increased temperature before and during the growth season inevitably strengthen the water stress by accelerating water consumption in the soil and trees through evaporation and transpiration, resulting in the formation of narrow rings, and vice versa. Reasonably, positive correlation of tree rings with monthly precipitation and negative correlations with monthly mean temperature in current growth year was identified in this study, and this climate-growth pattern was generally reported in the arid to semi-arid CLP (Gao et al, 2005;Liu et al, 2005; and other areas of northern China (Liang et al, 2007).…”
Section: Climate-growth Relationshipsupporting
confidence: 71%
See 2 more Smart Citations
“…Inversely, increased temperature before and during the growth season inevitably strengthen the water stress by accelerating water consumption in the soil and trees through evaporation and transpiration, resulting in the formation of narrow rings, and vice versa. Reasonably, positive correlation of tree rings with monthly precipitation and negative correlations with monthly mean temperature in current growth year was identified in this study, and this climate-growth pattern was generally reported in the arid to semi-arid CLP (Gao et al, 2005;Liu et al, 2005; and other areas of northern China (Liang et al, 2007).…”
Section: Climate-growth Relationshipsupporting
confidence: 71%
“…10) was very similar to the 38 yr cycle in the 2485 yr temperature reconstructions in the northeastern Tibetan Plateau , to the 35-38 yr cycle in a tree-ring-based streamflow reconstruction for the upper Yellow River (Gou et al, 2010) and to the 34.1 yr cycle in a tree-ring network-based spatial drought reconstruction for central high Asia (Fang , 2010b). Considering the limited length of our reconstruction (306 yr), the 102 yr cycle (p < 0.01) may not be reliable.…”
Section: Possible Linkage With Summer Asian-pacific Oscillation and Smentioning
confidence: 58%
See 1 more Smart Citation
“…Studies have also suggested that tree growth in arid to semiarid northern China is generally limited by a period of water deficit [9,10,24]. This relationship can frequently be reflected in the directly positive correlation between tree-ring width and rainfall over a given period.…”
Section: Discussionmentioning
confidence: 98%
“…Temperature (maximum temperature) affects the growth of trees by influencing the amount of moisture in the soil, as well as the respiration and transpiration rate of trees, especially if precipitation is not adequate during the growing season [6,23,24]. This pattern can often be inferred from tree-ring width chronologies that are positively correlated with rainfall and negatively correlated with temperature [25,26].…”
Section: Climate-growth Responsementioning
confidence: 99%